The Value of Multiple Medication Trials Prior to Balloon Sinuplasty in the Management of Chronic Sinonasal Disease - Shah, Anand G.; Ojeaga, Macaulay; Novak, Josephine; Honrubia, Vincent (International Archives of Otorhinolaryngology, 2023)
Introduction In patients with chronic rhinosinusitis, conservative interventions with extended medical trials are often attempted prior to procedural treatment. Balloon sinuplasty (BSP) is an established procedure for symptomatic relief from chronic rhinosinusitis. However, data suggesting the suboptimal efficacy of prolonged medication management trials, prior to BSP, is lacking.Objectives The purpose of this study was to evaluate the efficacy of prolonged medication management trials, prior to BSP, for patients with chronic rhinosinusitis.Methods A retrospective review was performed for all adults with chronic rhinosinusitis who received extended medical management prior to their BSP at two outpatient clinics, from November 1, 2013, to June 31, 2018. The patients' Sino-Nasal Outcome Test (SNOT) scores were compared between baseline, post-medication trials, and post-BSP.Results The SNOT scores of a total of 64 patients were collected. Overall, patients showed a significant worsening of symptoms during the medication management trials from baseline (p = 0.002126) but significant improvement of symptoms after undergoing BSP (p < 0.0001).Conclusion The patient symptom burden worsened and prolonged during medication management trials. The BSP procedure alone showed significant improvement in the quality of life for chronic rhinosinusitis patients, when considering their SNOT scores. The worsening of patients' symptoms during medication management may invalidate the necessity of prolonged medication management trials.
Keywords: rhinology; allergy; chronic rhinosinusitis; upper airway inflammation; otolaryngology; sinus surgery